KONTRUKSI MAKNA TRADISI MAUDU SEBAGAI IDENTITAS BUDAYA DALAM MASYARAKAT PESISIR DESA LAIKANG KABUPATEN TAKALAR - Sinta Dewi; Jumadi Sahabuddin; Abdul Rahman A. Sakka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Construction of the Meaning of the Maudu Tradition as a Cultural Identity in the Coastal Community of Laikang Village, Takalar Regency. Anthropology Education Study Program, Faculty of Social Sciences and Law, Makassar State University. Supervised by Jumadi Sahabuddin and Abdul Rahman A. Sakka. This study aims to find out 1. To find out why the Laikang Village community carries out the Maudu tradition 2. To find out the concept of siri of the Laikang Village community in studying the Maudu tradition 3. To find out what the meaning of the Maudu tradition is in the Laikang Village community. To achieve this goal, a qualitative research method was used by means of observation, interviews, and documentation.